A THEORETICAL STUDY ON AMBIVERT STUDENTS IN RELATION TO THE ACCURACY OF SYNTAX IN NARRATIVE WRITING - Ngatu, Simon P K (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2025)
The main purpose of this article attempts to explore theoritical framework of the impact of extrovert, introvert, and ambivert on the accuracy of syntax in narrative writing. Using the Systematic Literature Review (SLR) method, the present study find that the ambiverted students have a balance trait of personality (introvert and extrovert). The ambiverted students have a high concentration in doing writing task such as narrative writing. This is because they are able to communicate with themselves through reflection after involving in social interaction. This trait is different with introverted because ambiverted students have rich of knowledge because they acquire the knowledge through interaction with others in communication and have ability to go in deeper in reading task and reflection. This lead the ambivert students tend to do writing with with rich of vocabularies, they can put in a good sentences pattern (accuracy of syntax) and they have enough background of knowledge so they can do narrative writing easily and construct them in a good sentence (syntax).